2012
DOI: 10.1038/modpathol.2012.101
|View full text |Cite
|
Sign up to set email alerts
|

Fibrotic focus and hypoxia in male breast cancer

Abstract: Fibrotic focus is a scar-like lesion near the center of a carcinoma and has been associated with high-grade, lymph node metastases and poor survival in female breast cancers. Hypoxia is suggested to be the crucial link between fibrotic focus and aggressive tumor phenotype and is also itself a poor prognostic marker. We here set out to study fibrotic focus and hypoxia in male breast cancer for the first time. In a group of 134 male breast cancer patients, the presence and size of a fibrotic focus and the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
1
18
1
Order By: Relevance
“…Similarly, sporadic female breast cancers 6 showed a higher frequency of HIF1A positive tumors (50%) compared with sporadic male breast cancers in our study (28%), and comparable to the study by Kornegoor et al 18 (27%). A similar but less extreme difference is seen when comparing CA9 expression in male breast cancer and female breast cancer, 6,26 again in keeping with the findings of Kornegoor et al 18 We also only found seven cases (3%) that expressed both HIF1A and CA9. Although this is below the range seen in female breast cancer (11-23%), 6,27 it is not unexpected given the decreased staining of either marker when compared with female breast cancer and the known variability in HIF1A and CA9 half-lives.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Similarly, sporadic female breast cancers 6 showed a higher frequency of HIF1A positive tumors (50%) compared with sporadic male breast cancers in our study (28%), and comparable to the study by Kornegoor et al 18 (27%). A similar but less extreme difference is seen when comparing CA9 expression in male breast cancer and female breast cancer, 6,26 again in keeping with the findings of Kornegoor et al 18 We also only found seven cases (3%) that expressed both HIF1A and CA9. Although this is below the range seen in female breast cancer (11-23%), 6,27 it is not unexpected given the decreased staining of either marker when compared with female breast cancer and the known variability in HIF1A and CA9 half-lives.…”
Section: Discussionsupporting
confidence: 76%
“…Similarly, expression of the carbonic anhydrase IX (CA9) in female breast cancer has also been correlated with higher grade and poorer survival and is also overexpressed in triple negative (estrogen receptor negative, progesterone receptor negative, HER2 negative) tumors and associated with somatic loss of the BRCA1 protein. 17 There is only one study of hypoxic markers in male breast cancer, 18 comprising of 134 cases, which showed that 27% (34/ 125) and 7% (9/132) of cases demonstrated HIF1A and CA9 expression with HIF1A also associated with prognosis. 18 The study was not stratified into sporadic and familial cancers, and currently there are no data in familial male breast cancer, or whether similar changes of the hypoxic pathway are present in particular intrinsic phenotypes as shown in female breast cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor size and MAI were dichotomized using previously defined cutoff values. 15 Univariate survival analysis was done by plotting the Kaplan-Meier survival curves and performing the logrank test.…”
Section: Discussionmentioning
confidence: 99%
“…This group of patients was previously used to analyze the molecular sub-typing, fibrotic focus and hypoxia in male breast cancer. 14,15 The patients for whom survival data was not available were excluded in the current study. Age, tumor size and lymph node status were extracted from the pathology reports.…”
Section: Patientsmentioning
confidence: 99%